Internal control environment evaluation by means of maturity model in government organizations - Capovilla, Ricardo Augusto; Gonçalves, Rodrigo de Souza (Contextus - Revista Contemporânea de Economia e Gestão, 2018)
This work aimed to evaluate how mature the internal control environment is in governmental organizations. A maturity model was developed based on the principles of COSO (2013a), being structured into four levels of maturity: incipient, initial, developing and established. The model was assessed by judges (COY; DIXON, 2004) and tested in three governmental organizations by means of multiple-case studies. Just as indicated by results, one of the entities reached the initial maturity level, while the others reached the developing maturity level. Overall, the three organizations revealed incipience as to the maturity of the control environment, especially in spreading ethical standards and in due diligence and competency requirements for the governing body. Finally, the study points out, in a comparative way, aspects necessary to improve the internal control environment structures of each organization and can be useful to the respective managers and control bodies.